Vaccinium myrtillus L. Fruits as a novel source of Phenolic compounds with health benefits and industrial applications – a review - Pires, Tânia C.S. (2018)
Consumers’ demand for healthier foods with functional properties has had a clear influence on the food industry and in this sense, they have been attaching natural sources of bioactive ingredients into food products. Vaccinium myrtillus L. (bilberry) is known to be a functional food, presenting its fruits in the form of a small dark blueberry. This coloration is due to its high content in anthocyanin, being also associated with bilberries’ beneficial health effects. In the bilberry industry, there is a very high annual loss of this fruit due to the less aesthetic shape or appearance, in which they cannot be considered suitable for sale and are therefore disposed of as biological waste. Therefore, it is of great importance to valorize this fruit and this review aimed to completely characterize the fruits of V. myrtillus in order to comprehend the relationship between their consumption and the beneficial effects regarding consumer’s health. Thus, this review provides a description of the nutritional and bioactive compounds present in bilberry fruits, followed by their beneficial health effects. An overview of the natural pigments present in these fruits was also explored, focusing particularly in the anthocyanins composition, which represents the most widely studied class of bioactive compounds of V. myrtillus fruits. Finally, industrial applications of these fruits and by-products, as an efficient approach to the production of value-added products with economical and environmental impact, were also discussed. In general, V. myrtillus is a rich source of micronutrients and phytochemical compounds, such as organic acids, sugars, vitamins, fibers and phenolic compounds (anthocyanin and non-anthocyanin compounds), with nutritional and functional properties, that justify the growing interest in these berries, not only for food applications, but also in the pharmaceutical industry.